Method for testing atomic oxygen effect of nanoparticle material

By coating the nanoparticle suspension on the surface of quartz glass and irradiating atomic oxygen using atomic oxygen ground simulation equipment, the lack of atomic oxygen effect testing on nano-scale particulate matter was solved, and efficient and accurate test results were achieved.

CN119643429APending Publication Date: 2025-03-18BEIJING INST OF SPACECRAFT ENVIRONMENT ENG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411844438.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art lacks suitable test methods to test the effect of particulate matter on atomic oxygen on nanoscale or lower orders.

Method used

By coating the nanoparticle suspension on the surface of quartz glass passivation treated with atomic oxygen erosion, the samples were irradiated with atomic oxygen ground simulation equipment, and the parameters affecting atomic oxygen effects, such as residual rate and erosion thickness.

Benefits of technology

Atomic oxygen effect testing on nanoparticle materials is realized, which improves the accuracy and efficiency of the test, and can accurately measure the impact of atomic oxygen on nanoparticle materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119643429A_ABST
    Figure CN119643429A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of space environment, in particular to a nano-particle material atomic oxygen effect testing method which comprises the following steps: S1, coating a nano-particle suspension on the surface of quartz glass subjected to atomic oxygen denudation and passivation treatment, and drying to obtain a nano-particle material sample; s2, carrying out atomic oxygen irradiation on the nano-particle material sample in the step S1 by adopting atomic oxygen ground simulation equipment, and arranging a receiving disc below the nano-particle material sample; and S3, after the atomic oxygen is irradiated for a preset time, obtaining measurement data, and calculating atomic oxygen effect influence parameters. According to the method, the nano-particles are attached to the surface of the quartz glass by utilizing Van der Waals' force to form a stable nano-particle material sample, so that the atomic oxygen effect influence parameters can be accurately and efficiently measured, and the accuracy of testing the atomic oxygen effect of the nano-particle material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of space environment technology, and in particular to a method for testing atomic oxygen effects of nanoparticle materials. Background Art

[0002] Atomic oxygen refers to the residual gas environment in the form of atomic oxygen in low Earth orbit (usually considered to be 200km~700km altitude). Atomic oxygen is formed when ultraviolet light in sunlight interacts with oxygen molecules and decomposes them. The interaction between atomic oxygen and spacecraft can cause erosion and aging of spacecraft structural materials, damage spacecraft thermal control coatings, and seriously endanger the reliable operation of spacecraft, thereby causing very fatal damage to exposed components and materials of spacecraft, affecting its service life in orbit.

[0003] Currently, the materials of concern in atomic oxygen effect tests are all large-area materials such as films, paints, and cloths. There is a lack of suitable test methods for nanoscale or lower-level particulate matter.

[0004] In view of this, this application is specially filed. Summary of the invention

[0005] The present application provides a method for testing the atomic oxygen effect of nanoparticle materials, which is used to solve the problem of how to perform an atomic oxygen effect test on nanoparticle materials.

[0006] The present application provides a method for testing the atomic oxygen effect of nanoparticle materials, comprising the following steps: Step S1: coating a nanoparticle suspension on a quartz glass surface that has been subjected to atomic oxygen stripping and passivation treatment, and obtaining a nanoparticle material sample after drying; Step S2: using an atomic oxygen ground simulation device to irradiate the nanoparticle material sample in step S1 with atomic oxygen, and placing a receiving tray below the nanoparticle material sample; Step S3: After the atomic oxygen irradiation is performed for a preset time, measurement data is obtained, and atomic oxygen effect influencing parameters are calculated, wherein the atomic oxygen effect influencing parameters include the residual rate of the nano-particle material sample and the erosion thickness of the nano-particle material sample.

[0007] In some embodiments, the step S1, coating the nanoparticle suspension on the surface of the quartz glass subjected to atomic oxygen stripping passivation treatment, and obtaining the nanoparticle material sample after drying, comprises: Step S11: performing atomic oxygen stripping and passivation on the particle-bearing surface of the quartz glass; Step S12: weighing and recording the passivated quartz glass; Step S13: preparing a nanoparticle suspension; Step S14: spraying the nanoparticle suspension evenly onto the passivated quartz glass surface and performing a drying process to allow the nanoparticles to adhere to the quartz glass surface; Step S15: weighing and recording the quartz glass with the nanoparticles attached thereto.

[0008] In some embodiments, the nanoparticles are mixed with ethanol to form the nanoparticle suspension in step S13, wherein the content of the nanoparticles in the suspension is 0.004%-0.01%.

[0009] In some embodiments, in step S11, the beam current density is 5E+15 atoms / cm 2 •s, atomic oxygen acts vertically on the particle-bearing surface of the quartz glass with a kinetic energy of 5 eV±0.75 eV.

[0010] In some of the embodiments, in step S3, the surface microscopic morphology of the nano-particle material sample at the marked points is observed by surface electron microscopy to calculate the erosion thickness of the nano-particle material sample.

[0011] In some embodiments, in step S3, atomic oxygen acts perpendicularly on the surface of the nanoparticle material sample with a kinetic energy of 5 eV±0.75 eV.

[0012] In some embodiments, before step S2, the method further includes: Step S20: Calibrate the ground atomic oxygen simulation equipment, irradiate the atomic oxygen beam onto the surface of the Kapton sample fixed on the target, measure the erosion effect, record the test time, Kapton area, and weigh the Kapton mass before and after the test, and calculate the atomic oxygen flux density .

[0013] In some embodiments, the atomic oxygen flux density is calculated The following formula (1) is used: (1) In the above formula (1): is the value of atomic oxygen flux density, the unit is the number of atoms of oxygen per square centimeter per second [atoms / (cm 2 •s)]; The mass value of Kapton after the test, in grams (g); is the mass value of Kapton before the test, in grams (g); is the value of Kapton area, in square centimeters (cm2 ); The density of Kapton is 1.42, expressed in grams per cubic centimeter (g / cm 3 ); is the value of Kapton atomic oxygen stripping rate, which is 3×10 -24 , in cubic centimeters per atomic oxygen (cm 3 / atom); It is the exposure time of Kapton sample in atomic oxygen environment, in seconds (s).

[0014] In some of the embodiments, in step S2, the accumulated atomic oxygen flux to which the nanoparticle material sample is subjected is the product of the atomic oxygen flux density at that position and the sample test irradiation time.

[0015] In some embodiments, the residual rate R of the nanoparticle material sample is calculated using the following formula (2): (2) R is the residual rate of the nanoparticle material sample after atomic oxygen passivation treatment, unit is %; M glass is the mass value of quartz glass after atomic oxygen passivation treatment, in grams (g); M0 is the mass value of the sample carrying nanoparticle material before the test, in grams (g); M1 is the mass value of the sample carrying nanoparticle material after the test, in grams (g); M1 plate is the mass value of the nanoparticle receiving plate before the test, in grams (g); M2 plate The mass value of the nanoparticle receiving plate after the test, in grams (g) After adopting the above technical solution, the present application has the following beneficial effects compared with the prior art.

[0016] 1. The atomic oxygen effect test method of nanoparticle materials in this application uses van der Waals forces to attach nanoparticles to the surface of quartz glass to form a stable nanoparticle material sample, which can accurately and efficiently measure the parameters affecting the atomic oxygen effect and improve the accuracy of the atomic oxygen effect test of nanoparticle materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is a flow chart of a method for testing atomic oxygen effect of nanoparticle materials in the present application; Figure 2It is a logic block diagram of preparing nanoparticle material samples in this application; Figure 3 is a schematic diagram of the structure of the nanoparticle material sample before and after irradiation in this application; Figure 3 (a) shows the schematic diagram of the structure of the nanoparticle material sample before irradiation; Figure 3 (b) is a schematic diagram of the structure of the nanoparticle material sample after irradiation.

[0018] Figure 4 is a metallographic image of the nanoparticle material sample before and after irradiation at the marked point in the present application; Figure 4 (a) shows the metallographic image of the nanoparticle material sample at the marked point before irradiation; Figure 4 (b) shows the metallographic image of the nanoparticle material sample at the marked point after irradiation.

[0019] Figure 5 It is a schematic diagram of an atomic oxygen effect test of a nanoparticle material sample based on aluminum in the present application; Figure 5 (a) is a schematic diagram showing the structure of the base aluminum after atomic oxygen stripping passivation treatment; Figure 5 (b) shows the schematic diagram of the structure of the nanoparticle material sample; Figure 5 (c) is a schematic diagram of the structure of the nanoparticle material sample after irradiation.

[0020] Figure 6 It is a metallographic image of a nanoparticle material sample with quartz glass as the substrate at different irradiation times in the present application; Figure 6 (a) shows the metallographic image of the nanoparticle material sample based on quartz glass before irradiation; Figure 6 (b) shows the metallographic image of the nanoparticle material sample with quartz glass as the substrate after irradiation for 2h; Figure 6 (c) shows the metallographic image of a nanoparticle material sample based on quartz glass after irradiation for 4 hours. DETAILED DESCRIPTION

[0021] The technical solution of the present application will be described clearly and completely below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0022] like Figures 1 to 6 As shown, a method for testing the atomic oxygen effect of nanoparticle materials is provided in an embodiment of the present application, comprising the following steps: Step S1: coating a nanoparticle suspension on a quartz glass surface that has been subjected to atomic oxygen stripping and passivation treatment, and obtaining a nanoparticle material sample after drying; Step S2: using an atomic oxygen ground simulation device to irradiate the nanoparticle material sample in step S1 with atomic oxygen, and placing a receiving tray below the nanoparticle material sample; Step S3: After the atomic oxygen irradiation is performed for a preset time, measurement data is obtained, and atomic oxygen effect influencing parameters are calculated, wherein the atomic oxygen effect influencing parameters include the residual rate of the nano-particle material sample and the erosion thickness of the nano-particle material sample.

[0023] According to the atomic oxygen effect testing method of nanoparticle materials of the present application, nanoparticles are attached to the surface of quartz glass using van der Waals forces to form a stable nanoparticle material sample, which can accurately and efficiently measure the parameters affecting the atomic oxygen effect and improve the accuracy of the atomic oxygen effect testing of nanoparticle materials.

[0024] like Figure 2 As shown, in this embodiment, the step S1, coating the nanoparticle suspension on the surface of the quartz glass treated with atomic oxygen stripping and passivation, and obtaining the nanoparticle material sample after drying, comprises: Step S11: performing atomic oxygen stripping and passivation on the particle-bearing surface of the quartz glass; Step S12: weighing and recording the passivated quartz glass; Step S13: preparing a nanoparticle suspension; Step S14: spraying the nanoparticle suspension evenly onto the passivated quartz glass surface and performing a drying process to allow the nanoparticles to adhere to the quartz glass surface; Step S15: weighing and recording the quartz glass with the nanoparticles attached thereto.

[0025] During the simulated atomic oxygen test on the ground, the highly active atomic oxygen directly and vertically acts on the sample surface with a kinetic energy of 5 eV±0.75 eV. In order to ensure the accuracy of the final mass loss measurement results of the particulate matter in the atomic oxygen test, it is necessary to ensure that the nano-scale particles do not fall or are blown off by the impact of the atomic oxygen beam and that the particulate matter on the surface of the quartz glass is evenly distributed.

[0026] In a specific embodiment, the treated quartz glass surface is easy to be sprayed with particulate matter; when spraying the suspension, the mist of the suspension sprayed from the nozzle needs to be uniform; when spraying the suspension, it is necessary to spray once every 5 minutes to ensure that the nanoparticle material is evenly attached to the particulate matter bearing surface of the quartz glass.

[0027] In this embodiment, the nanoparticles are mixed with ethanol to form the nanoparticle suspension in step S13, wherein the content of the nanoparticles in the suspension is 0.004%-0.01%, which effectively meets the radiation test requirements of the nanoparticle materials and improves the accuracy and precision of the atomic oxygen effect test.

[0028] In this embodiment, in step S11, the beam current density is 5E+15 atoms / cm 2 •s, atomic oxygen acts vertically on the particle material bearing surface of quartz glass with a kinetic energy of 5eV±0.75 eV, which can achieve the purpose of both accurate simulation and accelerated evaluation of the erosion effect of nano-particle materials under the action of atomic oxygen.

[0029] In this embodiment, in step S3, the surface microscopic morphology of the nanoparticle material sample at the marked point is observed by surface electron microscopy to calculate the erosion thickness of the nanoparticle material sample, such as Figure 3 and Figure 4 As shown, by irradiating the marked points of the nanoparticle material sample with atomic oxygen, it can be seen that the nanoparticles attached to the particle material bearing surface of the quartz glass are gradually eroded under the action of atomic oxygen.

[0030] In this embodiment, before step S2, the method further includes: Step S20: Calibrate the ground atomic oxygen simulation equipment, irradiate the atomic oxygen beam onto the surface of the Kapton sample fixed on the target, measure the erosion effect, record the test time, Kapton area, and weigh the Kapton mass before and after the test, and calculate the atomic oxygen flux density , and then applied to the test of atomic oxygen effect of nanoparticle materials.

[0031] As an optional implementation, the atomic oxygen flux density is calculated The following formula (1) is used: (1) In the above formula (1): is the value of atomic oxygen flux density, the unit is the number of atoms of oxygen per square centimeter per second [atoms / (cm 2 •s)]; The mass value of Kapton after the test, in grams (g); is the mass value of Kapton before the test, in grams (g); is the value of Kapton area, in square centimeters (cm 2 ); The density of Kapton is 1.42, expressed in grams per cubic centimeter (g / cm 3 ); is the value of Kapton atomic oxygen stripping rate, which is 3×10 -24 , in cubic centimeters per atomic oxygen (cm 3 / atom); It is the exposure time of Kapton sample in atomic oxygen environment, in seconds (s).

[0032] In this embodiment, in step S2, the accumulated atomic oxygen flux to which the nano-particle material sample is subjected is the product of the atomic oxygen flux density at that position and the sample test irradiation time.

[0033] In this embodiment, the particle material damage results are measured and analyzed after the test, including the measurement of sample mass loss, the measurement of the mass change of the detached particle receiving plate, and the surface electron microscope observation of the microscopic damage of the particle material surface at the positioning point.

[0034] In this embodiment, the mass loss measurement refers to measuring the mass M of the quartz glass after atomic oxygen passivation treatment during sample preparation. glass , the weight of the sample after preparation M0, the mass of the falling particle receiving tray M1 plate After the atomic oxygen irradiation test, the sample mass is measured again M1 to obtain the sample mass loss M1-M0 and the receiving plate mass M2 plate , thereby calculating the residual rate R of the nanoparticle material sample.

[0035] As an optional implementation, the residual rate R of the nanoparticle material sample is calculated using the following formula (2): (2) R is the residual rate of the nanoparticle material sample after atomic oxygen passivation treatment, unit is %; M glass is the mass value of quartz glass after atomic oxygen passivation treatment, in grams (g); M0 is the mass value of the sample carrying nanoparticle material before the test, in grams (g); M1 is the mass value of the sample carrying nanoparticle material after the test, in grams (g); M1 plate is the mass value of the nanoparticle receiving plate before the test, in grams (g); M2 plate It is the mass value of the nanoparticle receiving plate that has fallen off after the test, in grams (g).

[0036] In this embodiment, the nanoparticles involved can be nano-scale carbon powder. A nano-scale carbon powder suspension is applied to a quartz glass surface that has been subjected to atomic oxygen stripping and passivation treatment, and then a nano-scale carbon powder sample is obtained after drying for an atomic oxygen test. The mass change of the nano-scale carbon powder sample is analyzed, and the sample residual rate of the nano-scale carbon powder sample is calculated. At the same time, the surface microscopic morphology of the nano-scale carbon powder sample at the marked point is observed, and the stripping conditions of the nano-scale carbon powder sample before and after the atomic oxygen test are compared and analyzed.

[0037] Nanoparticles Taking nano-scale carbon powder as an example, the specific implementation method of the atomic oxygen effect test method of nano-scale carbon powder sample is as follows: 1. Nano-scale carbon powder samples The nano-scale carbon powder sample comprises a nano-particle material sample with aluminum as a substrate and a nano-particle material sample with quartz glass as a substrate, wherein the nano-particle material sample with aluminum as a substrate is a control group, and the nano-particle material sample with quartz glass as a test group.

[0038] a) With a beam density of 5E+15 atoms / cm 2 •s, atomic oxygen acts vertically on the aluminum-based particle material support surface and the quartz glass particle material support surface with a kinetic energy of 5 eV±0.75 eV for 6 hours, and the passivated aluminum base and quartz glass are weighed and recorded as M Al 、M glass , M Al M is the mass value of the aluminum matrix after atomic oxygen passivation treatment, in grams (g); glass is the mass value of quartz glass after atomic oxygen passivation treatment, in grams (g); b) mixing nano-scale carbon powder with ethanol to form a nano-scale carbon powder suspension, and using a pressure nozzle to evenly spray the nano-scale carbon powder suspension onto the atomic oxygen passivation treated aluminum-based particle material bearing surface and the quartz glass particle material bearing surface, and then air-drying the nano-scale carbon powder so that the nano-scale carbon powder is attached to the atomic oxygen passivation treated aluminum-based particle material bearing surface and the quartz glass particle material bearing surface, thereby obtaining a nano-scale particle material sample with aluminum as the substrate and a nano-scale particle material sample with quartz glass as the substrate; c) Weigh the sample carrying nano-scale carbon powder and record it as M0, where M0 is the mass value of the sample carrying nano-scale carbon powder before the test, in grams (g); d) Observe the surface microstructure of the nano-scale carbon powder sample at the marked point.

[0039] 2. Atomic oxygen test a) Calibrate the ground-based atomic oxygen simulation equipment, where the beam density is 5E+15 atoms / cm 2•s, atomic oxygen acts vertically on the surface of the Kapton sample fixed on the target with a kinetic energy of 5 eV±0.75 eV, and the ablation effect is measured. The test time, Kapton area, and Kapton mass before and after the test are recorded, and the atomic oxygen flux density is calculated by formula (1): The accumulated atomic oxygen flux to the nanoscale carbon powder sample is the atomic oxygen flux density at that position. The product of the sample test irradiation time t; b) According to the calibration results of the ground simulation equipment, the prepared nano-scale carbon powder sample is placed in the direction of the atomic oxygen beam and mounted at a beam density of 5E+15 atoms / cm 2 •s position, install a temperature sensor on the target platform to monitor the sample temperature during the test, record the installation position, and close the door of the vacuum container; c) Conduct atomic oxygen experiments.

[0040] Test procedure: a. Start the measurement and control computer and the vacuum system to achieve a vacuum degree of 1.0×10 -3 Pa, start the sample stage temperature control system and heat sink system; b. Set various parameters according to the technical parameters during atomic oxygen beam density calibration and turn on the atomic oxygen source; c. Start timing after the atomic oxygen source works stably; d. After reaching the required atomic oxygen stripping time, turn off the atomic oxygen source; e. Close the vacuum system and fill it with high-purity nitrogen to re-pressurize; f. Open the door of the vacuum container and take out the test sample.

[0041] d) Weigh the sample, record the result, and calculate the sample residue rate.

[0042] e) Observe the surface microstructure of the sample at the marked points and compare and analyze the erosion of the sample before and after the test.

[0043] Performance Testing Nano-scale carbon powder sample residual rate: Atomic oxygen test is carried out on nano-scale carbon powder, and its mass change is analyzed to obtain the sample residual rate at the corresponding dose rate.

[0044] Surface micromorphology observation: The surface micromorphology of the nano-scale carbon powder samples before and after irradiation was observed using a surface electron microscope, and the erosion of the samples before and after the test was compared and analyzed.

[0045] Different aluminum substrates were subjected to atomic oxygen stripping and passivation treatment under the same conditions, and the aluminum substrate subjected to atomic oxygen stripping and passivation treatment was used as the substrate to obtain aluminum-based nano-scale carbon powder samples. The atomic oxygen effect test results of the aluminum-based nano-scale carbon powder samples are shown in Tables 1 and Figure 5 shown.

[0046] Table 1 Mass change of atomic oxygen test of nano-scale carbon powder samples based on aluminum

[0047] The quartz glass was subjected to atomic oxygen stripping and passivation treatment under the same conditions, and the quartz glass subjected to atomic oxygen stripping and passivation treatment was used as a substrate to obtain a nano-scale carbon powder sample with the quartz glass as a substrate. The atomic oxygen effect test results of the nano-scale carbon powder sample with the quartz glass as a substrate are shown in Tables 2 and Figure 6 shown.

[0048] Table 2 Changes in atomic oxygen test mass of nano-scale carbon powder samples based on quartz glass

[0049] From Table 1, Table 2, Figure 5 and Figure 6 It can be seen that when aluminum is used as the substrate, the carbon powder has low adhesion, which causes the carbon powder to detach during the test. When quartz glass is used as the substrate, the carbon powder is evenly sprayed on the particle material bearing surface of the quartz glass, which maximizes the uniform distribution of the carbon powder. Through the atomic oxygen test, photos were taken after 2h and 4h, respectively, and it can be seen that the carbon powder is gradually eroded, and at the atomic oxygen beam current of 5×10 15 Under the test conditions, the carbon powder loss reached 96.56% after 4 hours, achieving the atomic oxygen effect test result.

[0050] In the description of the present application, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.

[0051] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0052] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or communication with each other; it can be a direct connection, or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0053] In the present application, the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0054] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in the field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A method for testing atomic oxygen effect of nanoparticle materials, characterized in that: The following steps are involved: Step S1: coating a nanoparticle suspension on a quartz glass surface that has been subjected to atomic oxygen stripping and passivation treatment, and obtaining a nanoparticle material sample after drying; Step S2: using an atomic oxygen ground simulation device to irradiate the nanoparticle material sample in step S1 with atomic oxygen, and placing a receiving tray below the nanoparticle material sample; Step S3: After the atomic oxygen irradiation is performed for a preset time, measurement data is obtained, and atomic oxygen effect influencing parameters are calculated, wherein the atomic oxygen effect influencing parameters include the residual rate of the nano-particle material sample and the erosion thickness of the nano-particle material sample.

2. The method for testing the atomic oxygen effect of nanoparticle materials according to claim 1, characterized in that: The step S1, coating the nanoparticle suspension on the surface of the quartz glass treated by atomic oxygen stripping and passivation, and obtaining the nanoparticle material sample after drying, comprises: Step S11: performing atomic oxygen stripping and passivation on the particle-bearing surface of the quartz glass; Step S12: weighing and recording the passivated quartz glass; Step S13: preparing a nanoparticle suspension; Step S14: spraying the nanoparticle suspension evenly onto the passivated quartz glass surface and performing a drying process to allow the nanoparticles to adhere to the quartz glass surface; Step S15: weighing and recording the quartz glass with the nanoparticles attached thereto.

3. The method for testing the atomic oxygen effect of nanoparticle materials according to claim 2, characterized in that: The nanoparticles are mixed with ethanol to form the nanoparticle suspension in step S13, wherein the content of the nanoparticles in the suspension is 0.004%-0.01%.

4. The method for testing the atomic oxygen effect of nanoparticle materials according to claim 2, characterized in that: In step S11, the beam current density is 5E+15 atoms / cm 2 •s, atomic oxygen acts vertically on the particle-bearing surface of the quartz glass with a kinetic energy of 5 eV±0.75 eV.

5. The method for testing the atomic oxygen effect of nanoparticle materials according to claim 1, characterized in that: In step S3, the surface microscopic morphology of the nano-particle material sample at the marked points is observed by a surface electron microscope to calculate the erosion thickness of the nano-particle material sample.

6. The method for testing the atomic oxygen effect of nanoparticle materials according to claim 1, characterized in that: In step S3, atomic oxygen acts vertically on the surface of the nanoparticle material sample with a kinetic energy of 5 eV±0.75 eV.

7. The method for testing the atomic oxygen effect of nanoparticle materials according to claim 1, characterized in that: Before step S2, the method further includes: Step S20: Calibrate the ground atomic oxygen simulation equipment, irradiate the atomic oxygen beam onto the surface of the Kapton sample fixed on the target, measure the erosion effect, record the test time, Kapton area, and weigh the Kapton mass before and after the test, and calculate the atomic oxygen flux density .

8. The method for testing the atomic oxygen effect of nanoparticle materials according to claim 7, characterized in that: Calculate atomic oxygen flux density The following formula (1) is used: (1) In the above formula (1): is the value of atomic oxygen flux density, the unit is the number of atoms of oxygen per square centimeter per second [atoms / (cm 2 •s)]; The mass value of Kapton after the test, in grams (g); is the mass value of Kapton before the test, in grams (g); is the value of Kapton area, in square centimeters (cm 2 ); The density of Kapton is 1.42, expressed in grams per cubic centimeter (g / cm 3 ); is the value of Kapton atomic oxygen stripping rate, which is 3×10 -24 , in cubic centimeters per atomic oxygen (cm 3 / atom); It is the exposure time of Kapton sample in atomic oxygen environment, in seconds (s).

9. The method for testing the atomic oxygen effect of nanoparticle materials according to claim 1, characterized in that: In step S2, the accumulated atomic oxygen flux to which the nanoparticle material sample is subjected is the product of the atomic oxygen flux density at that position and the sample test irradiation time.

10. The method for testing atomic oxygen effect of nanoparticle materials according to any one of claims 1 to 9, characterized in that: The residual rate R of the nanoparticle material sample is calculated using the following formula (2): (2) R is the residual rate of the nanoparticle material sample after atomic oxygen passivation treatment, unit is %; M glass is the mass value of quartz glass after atomic oxygen passivation treatment, in grams (g); M0 is the mass value of the sample carrying nanoparticle material before the test, in grams (g); M1 is the mass value of the sample loaded with nanoparticle material after the test, in grams (g); M1 plate is the mass value of the nanoparticle receiving plate before the test, in grams (g); M2 plate It is the mass value of the nanoparticle receiving plate that has fallen off after the test, in grams (g).